Tectono‐Stratigraphic Evolution of the Kerguelen Large Igneous Province: The Conjugate William’s Ridge‐Broken Ridge Rifted Margins - Magri, L.; Whittaker, J. M.; Coffin, M. F.; Hochmuth, K.; Gürer, D.; Williams, S.; Bernardel, G.; Uenzelmann‐neben, G. (Journal of Geophysical Research: Solid Earth, 2024)
Extensive investigation of continental rift systems has been fundamental for advancing the understanding of extensional tectonics and modes of formation of new ocean basins. However, current rift classification schemes do not account for conjugate end members formed by Large Igneous Province crust, referring to thick mafic crust, sometimes including continental fragments. Here, we investigate the rifting of William's Ridge (Kerguelen Plateau) and Broken Ridge, components of the Kerguelen Large Igneous Province now situated in the Southeast Indian Ocean, and incorporate these end members into the deformation migration concept for rifted margins. We use multichannel seismic reflection profiles and data from scientific drill cores acquired on both conjugate margins to propose, for the first time, a combined tectono‐stratigraphic framework. We interpret seismic patterns, tectonic features, and magnetic anomaly picks to determine an across‐strike structural domain classification. This interpretation considers the rift system overall to be “magma‐poor” despite being located proximal to the Kerguelen plume but suggests that syn‐rift interaction between the Kerguelen mantle plume and the lithospheric structure of William's Ridge and Broken Ridge has controlled the along‐strike segmentation of both conjugates. We integrate seismic reflection and bathymetric data to test the hypothesis of predominantly transform motion, between the Australian and Antarctic plates, in Late Cretaceous and Paleogene time.